The Effect of Quality Costs on The Company Profitability Level at Pt. Kutai Timber Indonesia - fathor; Ainun , Moh. Baqir; Ghufrony, Ahmad; Fathor, Fathor (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
Quality costs are all costs incurred to handle a product quality problem. Profitability is the company's ability to earn profits from total assets sales and own capital. The objectives of this research are to recognize and analyze the effect of prevention costs on the company's profitability, to know and analyze the valuation costs effect on the company's profitability, to know and analyze the internal failure costs effect on the company's profitability, to know and analyze the effect of external failure costs on the company's profitability. Data analysis techniques in this study used validity and reliability tests to test the accuracy of research measuring instruments and measure the consistency of a series of measurements. Multiple linear regression analysis is used to determine whether there is an effect of prevention costs, assessment costs, internal failure costs, and external failure costs on the level of profitability. The model of the relationship between the level of profitability and these variables can be arranged in functions or equations. Based on the simultaneous/joint test that external failure costs have a large influence on the level of profitability. The product quality regression results have a value of 3,716 and an F count value (of 16,217), and the F table (3,111) with a significance level (0,000 <0.05). it explains that the company will be helped by the existence of projected goals and helps to manage all cost activities and redesign the mistakes that occur in the company. In addition, the company makes decisions about all cost events that will occur. Furthermore, the company always wants the existing costs in the company to be utilized efficiently